Investment of Tabung Masjid in Malaysia toward fulfilling Maqasid-Al-Shariah - Zakariyah, Luqman; Mhd. Sarif, Suhaimi; Mohd Nor, Azman; Ahmad H.Osman, Rahmah (Palgrave Macmillan, 2022)
This study aimed at providing insights on TM investment and its significance in fulfilling Maqasid-al-Shariah in the context of Malaysia. Two sets of hypotheses were formulated to test first, whether a significant difference exists in the intention to invest TM, and second, the causal relationship between TM investment and economic development indicators as proxies for three objectives of Shariah, that is, Tahadhib al-Fard Iqamah al-‘Adl and Al- Maslahah. Mosques are expected to conduct quality programmes according to Islamic principles, and the active involvement of community members in fund generation activities will increase the source of funds and increase the ability of mosques to meet such expectations. Good internal controls can enhance the transparency of mosques, which might enhance donors’ confidence to contribute more funds to mosques. This study indicates that mosque management should become concerned about the investment of surplus donations due to its relevance in achieving the greater objectives of the Shari’ah. Mosques in Malaysia have different strategies for investing TM and need to find a uniform platform for making a significant contribution to economic development. Several administrative and management issues must be looked into before empowering mosques to invest funds for the purpose of expanding their economic activities. Evidence provided by this study is based on personal opinions and forecasts, which may not portray the actual situation regarding TM investment. This study has identified the preferences of mosques in saving donations in Islamic banks but could not explore the possible reasons for such decisions. Future research on such issues will explain the preference towards faith-based banking among mosques in Malaysia.